Microencapsulation of white champaca (Michelia alba D.C.) extract using octenyl succinic anhydride (OSA) starch for controlled release aroma - Samakradhamrongthai R. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. The objective of the study was to optimise the encapsulation of Michelia alba D.C. (MAD) extract using octenyl succinic anhydride (OSA) starch. The MAD extract (5–10 g/100 g of dry starch) and the OSA starch (25–100 g/100 ml of water) was used in microcapsule preparation and analysed for the physicochemical and encapsulation properties. The optimised formula using the MAD extract and the OSA starch were 15.00 g/100 g of dry starch and 96.32 g/100 g water, which provided the highest in yield recovery (40.65% ± 0.99) and encapsulation efficiency (68.91% ± 1.50), with the lowest moisture content (3.19% ± 0.06) and water activity (0.236 ± 0.004). The aroma release from the optimum encapsulated powder in simulated artificial saliva fluid (SSF) suggested that linalool retention in microcapsules was higher than verbenone and 2-methyl butanoic acid. This study shows that the optimised formulation of MAD encapsulated flavour powder was found to be effective for controlling the aroma release.